Antifungal Activity of Mycogenic Silver Nanoparticles on Clinical Yeasts and Phytopathogens - Luiz Gustavo Ribeiro; Gabriella Sales Calaço Roque; Rafael Conrado; Ana Olívia De Souza (MDPI AG, 2023)
In this study, seven different silver nanoparticles (AgNPs) were obtained using the fungi species from the phylum Ascomycota, Aspergillus tubingensis, Aspergillus spp., Cladosporium pini-ponderosae, Fusarium proliferatum, Epicoccum nigrum, Exserohilum rostratum, and Bionectria ochroleuca, isolated from the Brazilian biodiversity, particularly from the mangrove and Caatinga biomes. The nanoparticles were coded as AgNP-AT, AgNP-Asp, AgNP-CPP, AgNP-FP, AgNP-EN, AgNP-ER, and AgNP-BO and characterized using spectrophotometry (UV-Vis), dynamic light scattering (DLS), zeta potential, transmission electron microcopy (TEM), and Fourier-transform infrared (FTIR) spectroscopy. All the AgNPs presented homogeneous size in the range from 43.4 to 120.6 nm (DLS) and from 21.8 to 35.8 nm (TEM), pH from 4.5 to 7.5, negative charge, and presence of protein coating on their surface. The antifungal activity of the AgNPs was evaluated on clinical strains of Candida albicans, and on the non-albicans species, Candida krusei, Candida glabrata, Candida parapsilosis, Candida tropicalis, and Candida guilliermondii, common in hospital infections, and against the phytopathogens Fusarium oxysporum, Fusarium phaseoli, Fusarium sacchari, Fusarium subglutinans, Fusarium verticillioides, and Curvularia lunata, which are species responsible for serious damage to agriculture production. The AgNPs were effective against the yeasts with MICs ranging from 1.25 to 40 µM and on the phytopathogens with MICs from 4 to 250 µM, indicating the promising possibility of application of these AgNPs as antifungal agents. The results indicated that the physicochemical parameters of the AgNPs, including the functional groups present on their surface, interfered with their antifungal activity. Overall, the results indicate that there is no specificity of the AgNPs for the yeasts or for the phytopathogens, which can be an advantage, increasing the possibility of application in different areas.